Ethics and Economics of Medical Supplies in the COVID-19 Pandemic - Li, Hansong; Wu, Yifei (European Scientific Journal, ESJ, 2021)
Background: The distribution of healthcare resources across local and global communities has triggered alarms throughout the COVID-19 pandemic. Injustice and inefficiency in the transfer of lifesaving medical supplies are magnified by the urgency of the public health crisis, ramified through pre-existing socioeconomic tensions, and further aggravated by frictions that plague international cooperation and global governance. Aim: This article explores the ethical and economic dimensions of medical supplies, from the microcosm of distributive algorithms to the macroscope of medical trade. Methods: It first analyses the performance, strategy, and social responsibility of ventilator-suppliers through a series of case studies. Then, the authors seek to redress the need-insensitivity of existing distributive models with a new price-based and need-conscious algorithm. Next, the paper empirically traces the exchange of medical supplies across borders, examines the effect of trade disputes on medical reliance and pandemic preparedness, and makes a game-theoretical case for sharing critical resources with foreign communities. Conclusion: The authors argue that the equitable allocation of medical supplies must consider the contexts and conditions of need; that political barriers to medical transfers undermine a government’s capacity to contain the contagion by reducing channels of access to medical goods; and that self-interested public policies often turn out to be counterproductive geopolitical strategies. In the post-pandemic world, the prospect of medical justice demands a balanced ethical and economic approach that cuts across the borders of nation-states and the bounds of the private sector and the public sphere.